Non-Contact Sensing Technologies for Intelligent Tire Condition Monitoring Using Laser Distance and IR Temperature Sensors (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Tyre degradation caused by tread wear and abnormal temperature rise directly affects vehicle safety, braking efficiency, and handling stability. Conventional tyre monitoring techniques primarily rely on manual inspection or pressure-based systems, which fail to provide continuous health assessment. This paper presents a real-time, non-contact Smart Tyre Health Monitoring System that simultaneously measures tyre tread depth and surface temperature. A VL53L0X Time-of-Flight laser distance sensor is used for accurate tread wear measurement, while an MLX90614 infrared sensor monitors tyre surface temperature without physical contact. Sensor data are processed using an Arduino microcontroller and continuously compared with predefined safety thresholds. Experimental evaluation demonstrates tread depth measurement accuracy within ±1 mm and reliable temperature monitoring up to 75 °C under dynamic conditions. Visual and audible alerts are generated when unsafe conditions are detected. The proposed system offers a low-cost, non-invasive, and scalable solution suitable for preventive maintenance and enhanced vehicle safety.